2013
DOI: 10.4049/jimmunol.1202304
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic Protein Noxa Regulates Memory T Cell Population Size and Protects against Lethal Immunopathology

Abstract: Memory T cells form a highly specific defense layer against reinfection with previously encountered pathogens. In addition, memory T cells provide protection against pathogens that are similar, but not identical to the original infectious agent. This is because each T cell response harbors multiple clones with slightly different affinities, thereby creating T cell memory with a certain degree of diversity. Currently, the mechanisms that control size, diversity, and cross-reactivity of the memory T cell pool ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
(72 reference statements)
1
25
1
Order By: Relevance
“…NKG2D promotes Mcl-1 induction and enhances survival early during memory cell commitment. In accordance with our observations, mice deficient for Noxa, the proapoptotic antagonist of Mcl-1, generate more memory cells upon influenza infection (36), stressing the importance of these proteins in memory cell formation. Our findings indicate that T cell vaccines will benefit greatly from persistent low-level NKG2D signaling to maximize the number of memory precursors that is allowed to form long-term memory.…”
Section: Discussionsupporting
confidence: 76%
“…NKG2D promotes Mcl-1 induction and enhances survival early during memory cell commitment. In accordance with our observations, mice deficient for Noxa, the proapoptotic antagonist of Mcl-1, generate more memory cells upon influenza infection (36), stressing the importance of these proteins in memory cell formation. Our findings indicate that T cell vaccines will benefit greatly from persistent low-level NKG2D signaling to maximize the number of memory precursors that is allowed to form long-term memory.…”
Section: Discussionsupporting
confidence: 76%
“…36,37 Noxa is activated by nutrient deprivation, potentially through maintenance of Mcl-1, 38 and can contribute to T-cell contraction in some model systems. 16,39 Further, we recently showed that Mcl-1 was critical for effector T-cell survival and that the additional loss of Bim failed to restore Mcl-1-deficient effector T-cell responses. 40 Thus, nutrients, by buffering Noxa with Mcl-1, and cytokines, by buffering Bim and Puma with Bcl-2, control the magnitude and persistence of the effector T-cell pool.…”
Section: Discussionmentioning
confidence: 99%
“…15 Noxa has a marginal role in contraction of T-cell responses. 16,17 Although Bim is the most dominant pro-apoptotic Bcl-2 family member driving contraction of T-cell responses, the study of T-cell responses to acute infection in Bim À / À mice is complicated by the ongoing autoimmune disease and altered negative selection in these mice. 18 Further, other data suggest that dendritic cell (DC) expression of Bim can control the magnitude of T-cell responses.…”
mentioning
confidence: 99%
“…Although it has been shown that the BIM/BCL-2 axis is a main regulator of the formation and maintenance of memory T cells, 26,27 NOXA has also been proposed to have a role in regulating the size and clonal diversity of memory T cell populations. 5,28 This is of particular interest as NOXA, like A1, is induced transcriptionally after TCR ligation. 5 NOXA is believed to antagonise MCL-1 to set a threshold for the survival of those CTLs with high-affinity TCRs.…”
mentioning
confidence: 99%